Responsive bystander behaviour in cyberbullying: a path through self-efficacy - Ferreira, P. C. (2020)
Bystander behaviour and self-efficacy beliefs play an important role in cyberbullying incidence. This study tested the relationship between the Bystander Intervention Model phases and the mediating role of adolescents’ self-efficacy beliefs. Children from the fifth to twelfth grade (N = 676) participated in this study by responding to questionnaires concerning the various phases of the Bystander Intervention Model and self-efficacy beliefs to resolve cyberbullying-related problems. Through structural equation modelling, noticing an incident of cyberbullying had a direct and indirect effect on aggressive behaviour, and an indirect effect on reporting and problem-solving behaviour. The indirect effect of interpreting the event through attributing responsibility was significant for aggressive and problem-solving behaviour. The mediator role of reflective decision-making had a stronger effect on direct problem-solving. Self-efficacy beliefs significantly affected the relationship between interpreting the event and all behaviour, but stronger for direct problem-solving. These findings help explain empirically how bystanders respond to incidents of cyberbullying.